The Relationship among Physical Activity, Intestinal Flora, and Cardiovascular Disease - Qiuyu Yan; Wenhui Zhai; Chenghao Yang; Zihao Li; Longfei Mao; Mingyi Zhao; Xiushan Wu (Cardiovascular Therapeutics)
Cardiovascular diseases (CVDs), which are associated with high morbidity and mortality worldwide, include atherosclerosis (AS), hypertension, heart failure (HF), atrial fibrillation, and myocardial fibrosis. CVDs are influenced by the diversity, distribution, and metabolites of intestinal microflora, and their risk can be reduced through physical activity (PA) such as regular exercise. PA benefits the metabolic changes that occur in the gut microbiota (GM). The major metabolites of the GM influence pathogenesis of CVDs through various pathways. However, the relationship between PA and GM is less well understood. In this review, we discuss the impacts of different types of PA on intestinal microflora including the diversity, distribution, metabolites, and intestinal barrier function including intestinal permeability, with a focus on the mechanisms by which PA affects GM. We also discuss how GM influences CVDs. Finally, we summarize current research and knowledge on the effects of PA on CVD via regulation of the GM and intestinal function. More understanding of relevant relationship between PA and GM may provide hope for the prevention or treatment of CVDs. Furthermore, a better understanding of regulation of the GM and intestinal function may lead to novel diagnostic and therapeutic strategies, improving the clinical care of CVD patients.